5/6 nephrectomy induces different renal, cardiac and vascular consequences in 129/Sv and C57BL/6JRj mice - Hamzaoui, Mouad (Sci Rep, 2020)
Experimental models of cardiovascular diseases largely depend on the genetic background. Subtotal 5/6 nephrectomy (5/6 Nx) is the most frequently used model of chronic kidney disease (CKD) in rodents. However, in mice, cardiovascular consequences of 5/6 Nx are rarely reported in details and comparative results between strains are scarce. The present study detailed and compared the outcomes of 5/6 Nx in the 2 main strains of mice used in cardiovascular and kidney research, 129/Sv and C57BL/6JRj. Twelve weeks after 5/6 Nx, CKD was demonstrated by a significant increase in plasma creatinine in both 129/Sv and C57BL/6JRj male mice. Polyuria and kidney histological lesions were more pronounced in 129/Sv than in C57BL/6JRj mice. Increase in albuminuria was significant in 129/Sv but not in C57BL/6JRj mice. Both strains exhibited an increase in systolic blood pressure after 8 weeks associated with decreases in cardiac systolic and diastolic function. Heart weight increased significantly only in 129/Sv mice. Endothelium-dependent mesenteric artery relaxation to acetylcholine was altered after 5/6 Nx in C57BL/6JRj mice. Marked reduction of endothelium-dependent vasodilation to increased intraluminal flow was demonstrated in both strains after 5/6 Nx. Cardiovascular and kidney consequences of 5/6 Nx were more pronounced in 129/Sv than in C57BL/6JRj mice.